Evaluation on quality control processes and procedures of Italit Construction and Development Corporation - Amis, Monnaliz; Balucan, John Paul.; Gamolo, Arturo; Macabingkil, Marianne (Diliman, Quezon City College of Engineering, 2001)
This paper studies the quality system of Italit Construction and Development Corporation in manufacturing polyvinyl chloride (PVC) pipes. This comprises the organizational structure, responsibilities, procedures, processes and resources for implementing quality management. Three quality-related problems were identified using Pareto Analysis. These were uneven thickness, cracked inside and burned line of PVC pipes. Using the Ishikawa Diagram, the root causes were found. Uneven thickness is caused by the imprecise placement of the die and the incorrect viscosity of the mixed raw materials. Cracked inside is caused by wrong temperature setting in the cooling bath. Burned line is caused by the defective pin heater which resulted to inaccurate temperature reading. Data is gathered by taking one sample per hour and measuring the pipe thickness in 8 points around its circumference. Using the data gathered from September of 2000 to March 2001 control charting was performed. The X and R charts plot the thickness of the 315 mm. Diameter pipes produced by the KMD machine. From these charts, it was discovered that the process was out of control but adequately capable. Aside from this, several c-charts were also used to determine the process variability of the nonconformities : uneven thickness, burned line and the number of nonconformities present in a batch. Again, the process as proven to be out of control. Knowing at this point that the process was out of control, interviews with the production and quality personnel were conducted so as to pin point the critical areas in the process that contributes greatly to the nonconformance of the pipe. The acceptance-sampling plan was also verified and analyzed. Italit employs a continuous type of sampling, which is done every hour. The quality costs were determined and evaluated by comparing it to the sales. Thirteen percent (13 percent) of its production costs was allocated to quality costs which was just enough to assure quality products. After careful analysis, it was recommended that the company should use CSP1 as their sampling plan and that they concentrate more on the prevention of defects to avoid incurring costs in reworks. Basing from the results of the analyses, recommendations and corresponding implementation guidelines were presented. For the case of uneven thickness and burned line, the group has suggested the use of a new calibration method with equipment settings checked every 180000 Kgs of output and having external raw material testing. For the cracked inside, the group has suggested to install a water cooling system and temperature gauge to regulate the temperature of the cooling bath. Lastly, for the case of the burned line in pipes, the group has suggested the calibration of equipment before each production run.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 135 : Industrial Quality Control
Keywords: Italit Construction and Development Corporation; Construction industries; Quality control